1986
DOI: 10.1007/bf00452062
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure in children, adolescents and young adults with Type 1 (insulin-dependent) diabetes

Abstract: Summary, Blood pressure has been measured by a single observer using a standardised technique in 163 Type I (insulindependent) diabetic patients aged 4 to 32 years, 232 of their non-diabetic siblings in the same age range and in 292 of their natural parents. Results for each sex were examined separately by analysis of variance. Systolic pressures were not significantly different overall nor in any single 4-year age band. In contrast, phase IV diastolic pressure was slightly but significantly higher in the diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Long-term strict metabolic control may delay or even prevent the progression of microalbuminuria to macroalbuminuria and overt diabetic nephropathy. Moreover, in terms of diabetic neuropathy, the recent reports from the DCCT study underline the benefit of intensive therapy in preventing the appearance of clinical neuropathy 4 . Therefore, maintenance of good metabolic control is the aim in children with IDDM, and particularly in those with early impairment of renal and neural function.…”
Section: Discussionmentioning
confidence: 98%
“…Long-term strict metabolic control may delay or even prevent the progression of microalbuminuria to macroalbuminuria and overt diabetic nephropathy. Moreover, in terms of diabetic neuropathy, the recent reports from the DCCT study underline the benefit of intensive therapy in preventing the appearance of clinical neuropathy 4 . Therefore, maintenance of good metabolic control is the aim in children with IDDM, and particularly in those with early impairment of renal and neural function.…”
Section: Discussionmentioning
confidence: 98%
“…Particularly, nocturnal hypertension may be important in terms of renal function deterioration (11). Data on BP monitoring in children and adolescents with insulin-dependent diabetes mellitus (IDDM) are limited and conflicting (12)(13)(14). Relatively elevated nocturnal BP was observed in a subgroup of normoalbuminuric diabetic children and was attributed to autonomic dysfunction (14).…”
Section: Introductionmentioning
confidence: 99%
“…In all but one study no difference in BP was observed between healthy controls and patients with normoalbuminuric type 1 diabetes, when adjusting for albuminuria, diabetes duration, age and gender. 3,4,11,12,14,16,[25][26][27] We have used an automatic auscultatory device (Profilomat ® ) to measure 24-h BPs and found no significant difference in 'daytime' or 'night-time' BP or in systolic or diastolic day-night differences between diabetic patients and controls. These results are somewhat in contrast with data from studies in which 24-h BPs were measured with an oscillometric device.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results have been reported regarding the prevalence of hypertension in patients with normoalbuminuric IDDM, showing either a slightly higher than expected or a normal percentage of IDDM patients with elevated BP. [7][8][9][10][11][12] Some investigators have reported that even in young diabetic patients BP is increased, 9,10 but others did not find a difference in systolic BP between diabetic children and a reference population whereas diastolic BP tended to be even lower. 11 Although most cross-sectional as well as longitudinal studies on the prevalence of elevated BP in type 1 diabetes suggest an association between microalbuminuria and BP rise, it is still controversial whether the increase of arterial BP precedes, follows or develops in parallel with the onset of microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation